Unphosphorylated STAT5A stabilizes heterochromatin and suppresses tumor growth - Hu, Xiaoyu (National Academy of Sciences, 2013)
Tumor suppressors known to date impede cancer growth by arresting the cell cycle or promoting apoptosis. Here we show that unphosphorylated human STAT5A functions as a tumor suppressor capable of repressing multiple oncogenes via heterochromatin formation. Unphosphorylated STAT5A binds to heterochromatin protein 1α (HP1α) and stabilizes heterochromatin. Expressing unphosphorylated STAT5A or HP1α inhibits colon cancer growth in mouse xenograft models. Transcriptome profiling shows that expressing an unphosphorylatable STAT5A has similar effects to overexpressing HP1α in global gene expression. Notably, the majority of the genes commonly repressed by unphosphorylated STAT5A and HP1α have been implicated in cancer development. Finally, down-regulation, somatic mutations, and deletions of STAT5 genes are found in certain human cancers. These results suggest that unphosphorylated STAT5A may epigenetically suppress tumor growth by promoting heterochromatin formation.